A COMPARATIVE STUDY OF THE RUSSIAN AND UZBEK CASE SYSTEMS: STRUCTURAL FEATURES AND TRANSLATION CHALLENGES - N.P. Dustmamatova; F.Sh. Uzakova (International Journal of Literature and Language Studies, 2026)
Abstract. This article examines the case systems of the Russian and Uzbek languages from a comparative perspective. It analyzes the principal similarities and differences in the expression of case meanings, which arise from the typological distinction between Russian as an inflectional language and Uzbek as an agglutinative language. Particular attention is paid to the translation challenges encountered when rendering Russian case forms into Uzbek and vice versa. The study discusses methods of translating the Russian instrumental, prepositional, and genitive cases and identifies the most common errors made by Uzbek-speaking learners of Russian. The findings demonstrate that the successful translation of case constructions requires consideration not only of grammatical form but also of semantic meaning and contextual usage.